Analysis of Implementation of Fugel Models of Innovation at BKI Academy - Rukmana, Dandy; Hardjono, Retno Kusumastuti (Manunggal Halim Jaya, 2025)
Successful innovation in today's business world requires an integrated approach, encompassing aspects of corporate design, product design, and the application of new technologies. Effective collaboration and targeted design management are key to achieving successful innovation. Utilizing efficient knowledge management techniques and tools in integrated design efforts is also important. Proactive planning is critical in innovation, where companies must integrate market trends, competition, emerging technologies, and changing customer preferences. Companies should not just wait for innovation to come by chance, but instead plan proactively and create an environment that encourages innovative thinking. The emergence of BKI Academy as a relatively new organization poses a significant challenge. The concept of BKI Academy itself as a provider of training and MICE services in the Maritime, K-3, Energy, Testing, Inspection & Certification, Construction, Management Systems and Human Resources market categories for all industries related to a unique value proposition for professionals and students in Indonesia, because maritime education/training institutions in Indonesia are minimal, BKI Academy sees this as a very appropriate opportunity. It is beneficial for the needs of workers in the maritime world. The innovation process plays a role in the development of companies or institutions. In an era where the flow of information and communication is growing rapidly, consumers are increasingly savvy in choosing products and services. Therefore, BKI Academy and similar organizations must continue to innovate and adapt to the times to meet customer needs and ensure the continuity of their business in an increasingly competitive market. The data collection technique used is the documentation technique. The data analysis design used is descriptive analysis. This study will provide an in-depth overview of how innovation models are applied at BKI Academy and how they impact the organization's progress. It will also provide the best recommendations for maritime educational institutions in building entrepreneurship-based education.